The Disjuncture between Gendered Legislation and the Practice of Urban Planning: A Case Study of the Swaziland Urban Development Project. (March 2014) - Simelane, Hloniphile Y.
Abstract This study examines the disjuncture between gender‐neutral legislation, state policies in particular, and the implementation of the Swaziland Urban Development Project (SUDP), an integrated development project co‐funded by the World Bank and the Swaziland government. The project provided the opportunity to introduce gender‐neutral land‐related policies to improve women's access to land ownership in informal settlements. Using qualitative research methods and empirical evidence from the SUDP, this study assesses the environment in which patriarchal practices are reinforced. The study also advocates the formulation of gendered policies and a review of the institutions and structures underlying social relations and the control of resources. It argues that legislative measures alone are insufficient to improve the status of women in terms of land ownership. Finally, the study proposes the necessary policy conditions in which the SUDP's gender‐neutral approach can effectively foster land redistribution.